Gossypiboma: case report and review of literature - Ram, Tulasi; Dahiya, Divya; Naik, Anil (International Surgery Journal, 2019)
Gossypiboma or retained surgical sponge is an entirely preventable surgical complication; it is associated with significant morbidity to patient and medico legal issues to the surgeon. Clinical presentation depends upon location of the foreign body and tissue reaction to the foreign body. Pre-operative diagnosis is the most difficult part and treatment of choice is surgery. A 30 year female presented with 16 months history of gradually increasing lump on left side of lower abdomen following a caeserian section. Ultrasonography was suggestive of infected mesenteric cyst and contrast enhanced computed tomography scan of abdomen was suggestive of either chronic abscess or gossypiboma. She was treated surgically; intra-operatively there was a 10×10 cm well circumscribed lesion in sigmoid mesentery which was adherent to sigmoid colon. It was a single surgical sponge with about 1000 ml of pus. Gossypiboma is an entirely avoidable surgical complication which is associated with significant morbidity and medico-legal implications. Meticulous counts with thorough exploration of site before closure can lessen the undue morbidity or mortality. Radio frequency identification verification by barcode scanner can reduce the error rate.